Contributions to Balkan bibliography: World bibliographical series, vol.59: Romania, compiled by Andrea and Dennis Delatant. Vol.94: Albania, compiled by William B.Bland. Vol.107: Bulgaria, compiled by Richard J.Crampton. Vol.1: Yugoslavia - Kitromilides, Paschalis M. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1990)
[ Δε διατίθεται περίληψη / no abstract available]